The impact of economic conditions in Sudan on the drop out of students and their involvement in the labor market from the point of view of educational supervisors "Applied Study on Students of General Education Schools in Local Medani district" - Al Tarifi, Muhied Abdullah (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to identify the impact of economic conditions in Sudan on the leakage of students and their involvement in the labor market from the point of view of educational supervisors in the district of Madani Al- Kubra. The aim was to identify the most important economic reasons affecting leakage, The sample size (40) supervisors and supervisors were selected randomly, and the analytical descriptive method was applied. The study came out with a number of results, the most important of which is that economic reasons play a major role in causing the dropout problem among general education students. Rh in the spread of the phenomenon of child labor in the Middle education students Am.oon leakage phenomenon spread among males more than females, And that secondary students are more leaking than students at the basic stage. The most economical reasons contributing to the dropout of students are the difficult living conditions faced by the family and the inability to pay the school expenses. The study also showed that there are no differences between the average responses of the study sample: (Type, qualification, experience, specialization, number of courses)